Sailing around the UK and Ireland - Oliver, Roger (Practical boat owner, 2011)
This new book, based on a highly successful series of articles in Practical Boat Owner magazine, is a detailed practical guide to sailing around the UK - all by means of day sails. Roger Oliver, a passionate sailor, explains his in-depth passage planning, boat preparations, weather checks and log-keeping, as well as his choice of routes, detailed navigation, sail trim tips and on-passage maintenance, all for the benefit of sailors who have a yen to follow in his footsteps. Packed with a wealth of practical tips on seamanship, anchoring in high winds, coping with big seas, problem-solving, harn.